Potret Kebutuhan Bahan Ajar IPAS Berbasis Aplikasi Android: Hasil Studi Kuantitatif dan Kualitatif di Lingkungan SD Kecamatan Pemalang - Bayu, Bayu Noviansyah; Purwo, Purwo Susongko; Nugraha, Rahmad Agung (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to analyze the needs for developing Android-based instructional materials for Natural and Social Sciences (IPAS) at the elementary school level in Pemalang Regency. The research employs a descriptive quantitative approach using proportional cluster random sampling, involving principals, teachers, students, and parents as respondents. Data were collected through Likert-scale questionnaires and semi-structured interviews, and then analyzed using both quantitative and qualitative descriptive methods. The results reveal that all respondent groups expressed positive responses toward the need for developing Android-based digital learning materials. Principals and teachers believed that digital media could overcome the limitations of conventional teaching methods, while students showed high enthusiasm for interactive and flexible learning media. Parents also strongly supported the use of digital media for independent learning at home. These findings affirm that developing Android-based IPAS learning materials is seen as a strategic solution to enhance the effectiveness, engagement, and quality of IPAS learning in elementary schools. The implications of this study highlight the importance of providing digital facilities, teacher training, and active collaboration between schools and parents to build a technology-based learning ecosystem that is adaptive to the digital era.